NATURE AND NATURALISM IN CLASSICAL GERMAN PHILOSOPHY ([S.l.])
1 online resource
Keywords: This book offers the first comprehensive exploration of the relevance of naturalism and theories of nature in Classical German Philosophy. It presents new readings from internationally renowned scholars on Kant, Jacobi, Goethe, the Romantic tradition, Fichte, Schelling, Hegel, and Marx that highlight the significance of conceptions of nature and naturalism in Classical German Philosophy for contemporary concerns. The collection presents an inclusive view: it goes beyond the usual restricted focus on single thinkers to encompass the tradition as a whole, prompting dialogue among scholars interested in different authors and areas. It thus illuminates the post-Kantian tradition in a new, wider sense. The chapters also mobilize a productive perspective at the intersection of philosophy and history by combining careful textual and historical analysis with argument-based philosophizing. Overall, the book challenges the stereotypical view that Classical German Philosophy offers at best only an idealistic, one-sided, anachronistic, and theological view of nature. It invites readers to put traditional views in dialogue with current discussions of nature and naturalism. Nature and Naturalism in Classical German Philosophy will be of interest to scholars and advanced students working on Classical German Philosophy, 19th-Century Philosophy, and contemporary perspectives on naturalism.